Improvements of oil-in-water analysis for produced water using membrane filtration - Khor, Ee Huey (Curtin University, 2011)
The accuracy of oil-in-water analysis for produced water is increasingly crucial as the regulations for disposal of this water are getting more stringent world wide. Currently, most of the oil producing countries has their own regulations for disposal of this water. The oil-in-water can be distinguished between two types, mainly dispersed and dissolved oil. Among these oils, dispersed oil concentration is the main component under monitoring for the oil-in-water limitation. From literatures, the standard analytical method for oil-in-water measurement has been changed from IR analysis to GC-FID analysis due to solvent restrictions. As a result of the change, a total of dispersed and dissolved oil is measured and this causes the oil-in-water parameter value to be higher. Therefore the removal of dissolved oil before oil-in-water analysis is critical. This issue can be overcome by enhancing current monitoring technique which incorporates a separation technique in removing dissolved oil from the produced water prior to the GC-FID analysis.A thorough review was given to all current available separation techniques that can be employed for dissolved oil removal. Membrane filtration system was proposed in this research to be incorporated into the test method to remove the dissolved oil as it is relatively a small separation unit, easy to operate and very practical in the laboratory scale application. By using membrane filtration, it was found that the removal of dissolved oil is dependent on the pore-size of the membrane where in this case Microfiltration removes more dissolved oil than Ultrafiltration.However, there is an issue in using this membrane filtration technique. The deposition of dispersed and dissolved oil on the membrane reduces the efficiency of the removal process. In this research, mathematical & computational modelling was done in studying the hydrodynamic effect caused by pressure for the fluid flow profile inside the membrane cartridge. Then, two approaches are proposed prevention of fouling, firstly, by physical or mechanical means and secondly, by chemical means. The use of mechanical means for the prevention of deposition were studied by simulation using computational fluid dynamics (CFD) and mathematical model to visualize the hydrodynamic conditions inside the membrane cartridge.Mathematical model has been developed for the relationship of differential pressure(DP) with the concentration of oils at the wall (Cg). The purpose of this study is toestimate the concentration of oils by changing the differential pressure. Severalfactors for the reduction of fouling or the concentration of oils at the membrane wallby physical means such as pore sizes, membrane types and operating conditions werestudied. The experimental data were analyzed by using statistical method. Throughdesign of experiment (DOE) and the verification of CFD visualization, the optimumconditions for the operation were identified to be at low differential pressure (DP)but at high trans-membrane pressure (TMP). The most suitable type of membranewith 0.2um pore size was found to give highest efficiency in removing dissolved oil.Despite these findings, the total prevention of oil fouling on the membrane by mechanical means is not possible. Therefore, chemical pre-treatment method and chemical cleaning methods were explored in their capacity to remove the deposition of oil on the membrane. This pre-treatment method enhances the separation by changing the physical properties of the oil towards the membranes. Changes of chemical properties of oil should be avoided in this attempt for accuracy of measurement. pH changes are one of the ways for pre-treatment, and the effects of acidity and alkalinity effect on the solution were studied for the improvement of the separation.Chemical cleaning using NaOH was investigated for its ability to clean off the deposition of oils on the membrane. The duration of the cleaning as well as the volume used were studied experimentally until the optimum conditions were reached. The chemical treatment approaches are integrated into the physical method to enhance the removal of dissolved oil by using membrane filtration. The optimum condition of this integrated techniques were verified experimentally.In conclusion a new standard analysis method in the oil-in-water parameter monitoring for produced water in the oil and gas sector has been developed. With the incorporation of membrane filtration system, produced water analysis will be improved, which would benefit the oil and gas operators.